Multi-agent simulation of competitive electricity markets: Autonomous systems cooperation for European market modeling. (15th July 2015) - Santos, Gabriel; Pinto, Tiago; Morais, Hugo; Sousa, Tiago M.; Pereira, Ivo F.; Fernandes, Ricardo; Praça, Isabel; Vale, Zita
Highlights: Definition of an ontology allowing the communication between multi-agents systems. Social welfare evaluation in different electricity markets. Demonstration of the use of the proposed ontology between two multi-agents systems. Strategic biding in electricity markets. European electricity markets comparison. Abstract: The electricity market restructuring, and its worldwide evolution into regional and even continental scales, along with the increasing necessity for an adequate integration of renewable energy sources, is resulting in a rising complexity in power systems operation. Several power system simulators have been developed in recent years with the purpose of helping operators, regulators, and involved players to understand and deal with this complex and constantly changing environment. The main contribution of this paper is given by the integration of several electricity market and power system models, respecting to the reality of different countries. This integration is done through the development of an upper ontology which integrates the essential concepts necessary to interpret all the available information. The continuous development of Multi-Agent System for Competitive Electricity Markets platform provides the means for the exemplification of the usefulness of this ontology. A case study using the proposed multi-agent platform is presented, considering a scenario based on real data that simulates the European Electricity Market environment, and comparing its performance using different market mechanisms. The main goal is to demonstrate the advantages that the integration of various market models and simulation platforms have for the study of the electricity markets' evolution.